Chemical characterization and sources of PM2.5 at a high-alpine ecosystem in the Southeast Tibetan Plateau, China. (15th August 2020) - Meng, Ya; Li, Rui; Zhao, Yilong; Cheng, Hanyun; Fu, Hongbo; Yan, Zhe; Bing, Haijian
Abstract: The study of atmospheric chemical compositions in remote areas is of great significance for understanding the biogeochemical impact of atmospheric dry deposition on ecosystems. In this study, a total of 50 p.m.2.5 samples were collected at a high alpine forest of Mt. Gongga, Eastern Tibetan Plateau from May 2015 to May 2016 to investigate the characteristics of PM2.5 mass concentration and its major compositions including elemental carbon (EC), organic carbon (OC), and 24 trace elements. The average PM2.5 mass concentration was 17.19 ± 8.81 μg/m 3, which was at an intermediate level compared with other areas of Tibetan Plateau. The yearly average concentrations of OC and EC were 2.98 ± 1.95 and 0.43 ± 0.33 μg/m 3, accounting for 19.49% and 2.51% of PM2.5 mass, respectively, and the sums of the total concentrations of the 24 analyzed trace elements were 3.70 ± 0.80 μg/m 3, accounting 27% of PM2.5 mass concentration. PM2.5, EC and OC showed the higher concentrations and larger fluctuation in the dry season (October 2015 to May 2016) compared with those in the wet season (June 2015 to September 2015), which was attributed to the multiple factors including the increases of biomass burning and fossil fuel emissions, the relatively shallow boundary layer height and lower temperature, and the less precipitation. Two distinct seasonal patterns were observed for the 24 analyzed trace elements in PM2.5 : the crustal-derived trace elements like Fe, Al, Mn and Sr showed the higher concentrations in the wet season, while anthropogenic-derived elements such as Cd, Pb, Ni and Zn exhibited the higher level during the dry season. Six sources were identified for PM2.5  at Mt. Gongga with the application of the positive matrix factorization (PMF). Biomass burning (27.06%) and crustal source (26.93%) were the two main sources, followed by secondary formation (16.41%), traffic-related source (12.89%), coal burning (10.57%) and industrial metallurgical process (6.15%). Finally, it was proposed that the atmospheric acidic processing could not only promote the dissolution of Fe, but also enhance the solubility of the other trace elements in the atmosphere during the transport. Accordingly, this would increase the bioavailability and/or toxicity to the biotic and plants. Highlights: PM2.5, EC, OC and some anthropogenic elements showed the higher concentrations and larger fluctuation in the dry season. The elevated crustal trace elements in the wet season were linked to the soil dust from Sichuan Basin and Tibetan soils. Biomass burning and crustal source explained 27.06% and 26.93% of the total species, respectively.